Towards the constitutional democracy in Vietnam: an analysis of the constitutional amendment of 2013 - Dang, Tuan Minh (Đại học Quốc gia Hà Nội, 2020)
The constitutional developments in Vietnam since “Doi moi” (Renovation) of 1986 show the trend of its transition towards the constitutional democracy. While maintaining the principles of socialist democracy, Vietnam has tried to adopt many new progressive democratic values. This is in line with the trend of reforms in transitional democracies, especially in East Asian countries. However, compared to those countries that have made strong reforms, Vietnam is still recognized to be the follower with little changes. While comparing to the current socialist democracies like China, Vietnam has a clearer and more progressive approach towards constitutional democracies instead of trying to build a separate model.1 This article aims to demonstrate the process of constitutional transformation through the analysis of the 2013 Constitution. The approach of this paper does not follow the interpretation of a model of constitutional democracy for Vietnam but instead proves the need, possibility, and value of Vietnam in adopting more principles of constitutional democracies. The academic contribution of this study is to affirm some previous studies about “the global constitution-making process”2 of Vietnam3, but is also to argue that this process has not really brought significant changes to the constitutional democracy due to the lack of a constitutional review mechanism to make the Constitution be enforced in society.